Regional development and spatial equity in Northern Ireland - Goodyear, P.M.; Eastwood, D.A. (Economic & Social Studies, 1979)
The paper examines Northern Ireland's `regional strategy? programme, assessing its successes and failures in reducing spatial inequalities in overall social well-being throughout the province. Social well-being is calculated using a widely modified version of Knox's `level of living? index. The present position and recent trends of spatial inequality are reviewed, both between rural and urban areas and within urban areas. The lack of a satisfactory system for monitoring Northern Ireland's regional strategy is also highlighted.
Keywords: Regional strategy - Northern Ireland; Social well-being - Northern Ireland